Peristiwa Teater Tu(M)Buh Sebagai Konstruksi Politik Tubuh - Andi Taslim Saputra; I Nyoman Murtana (LP2M ISBI Bandung, 2019)
ABSTRACT Body politics is often stigmatized in the context of community and government institutions, such as the military, hospitals, prisons, etc. This study shows the body politics in different contexts. This study reads the theater phenomenon that gave birth to the body's political form in the context of theater with the focus of case studies of process Tu(m)buh by Tony Broer's. The application of Tony Broer's theater work differs from that of other theaters, the idea of the body's political construction. To read the question of Tony Broer's political practice using Foucault's disciplinary power concept. This research uses descriptive analytic research method. Data collection was done through observation, documentation, interview, and data analysis. The result showed, Tony Broer execute body politic practice in the event of Tu(m)buh theater. The formation of Tony Broer's body construction is disciplined and body forming that intense, hard, and radical. Tony Broer's actions gave birth to concepts and practices that show the body's political image, both to oneself and to others, to the theater of Tu(m)buh as the presentation of the body's political construction.Keywords: Theater, Body Politics, Tu(m)buhABSTRAK Politik tubuh kerap distigmakan dalam konteks institusi-institusi kemasyarakatan dan pemerintah, misalnya militer, rumah sakit, lapas, dan sebagainya. Kajian ini memperlihatkan politik tubuh dalam konteks berbeda. Penelitian ini membaca fenomena teater yang melahirkan bentuk politik tubuh fokus studi kasus peristiwa Tu(m)buh karya Tony Broer. Penerapan kerja teater Tony Broer berbeda dari pelaku teater lainnya, yakni gagasan politik tubuh. Untuk membaca persoalan praktik politik tubuh Tony Broer menggunakan konsep disciplinary power Foucault. Penelitian ini menggunakan metode penelitian deskriptif analitik. Pengumpulan data dilakukan melalui observasi, dokumentasi, wawancara, dan analisis data. Hasilnya menunjukkan, Tony Broer melaksanakan praktek politik tubuh dalam peristiwa teater Tu(m)buh. Pembentukan kontruksi tubuh Tony Broer berupa pendisiplinan dan pembentukan tubuh yang intens, keras, dan radikal. Tindakan Tony Broer melahirkan konsep dan praktis yang memperlihatkan citra politik tubuh, baik terhadap diri sendiri dan atas orang lain, sehingga peristiwa teater Tu(m)buh sebagai kerja teater presentasi politik tubuh.Kata Kunci: Teater, Politik Tubuh, Tu(m)buh.